New efficient ligand for sub-mol % copper-catalyzed C–N cross-coupling reactions running under air - Larsson, Per-Fredrik; Astvik, Peter; Norrby, Per-Ola (Beilstein Journal of Organic Chemistry, 2012)
A new efficient ligand, N,N’’-dimethyldiethylene triamine (DMDETA), has been synthesized and evaluated for sub-mol % copper-catalyzed C–N cross-coupling reactions. The efficiency of the ligand was determined by kinetic methods. DMDETA proved to display efficiency similar to DMEDA and, in addition, the resulting catalyst was tolerant to air.
Keywords: copper; cross coupling; hyperactivity; kinetics; ligands